The Relationship Between Time Allocation for Work and Personal Life and Happiness - Tauraitė, Viktorija; Aleksandravičienė, Akvilė (Social Welfare: Interdisciplinary Approach, 2023)
The aim of the article is to identify the relationship between time allocation for work and personal life and happiness by reviewing the theoretical aspects of time allocation for work and personal life and happiness and by presenting an empirical research methodology. A review of the scientific literature is carried out using a comparative analysis and a generalisation method. Empirical research was conducted using statistical data, correlation analyses, non-parametric Mann-Whitney U test, X2 criterion, and data collection methods: questionnaire and time diary. The number of respondents is 1073, the studied population is self-employed persons in Lithuania. Empirical evidence shows that in 2019, self-employed people in Lithuania spent 77.5 percent of their daily time on their personal life (mostly to sleep and leisure) and 22.5 percent on work. With a 95 percent probability, it was found that the time spent on sleep (08:41) by 15-24-year-olds is statistically significantly different from other age groups (H11 confirmed). Although self-employed individuals were most likely to be happy, satisfied with work and satisfied with their personal life in 2019, but those aged 15-24 were the happiest. However, men were more satisfied with work and women were more satisfied with their personal life. There was a statistically significant relationship at a 95 percent confidence level between the level of work-life balance of the self-employed person and happiness (H21 confirmed).